Initial evaluation of children admitted on the Paediatric Intensive Care Unit - Esperanza Arce Delgado; Raquel Bravo López; Mónica Díaz López; Beatriz Etura Azpillaga; María Teresa Martín Alonso; María Teresa Martín Alonso (Fundación para el Desarrollo de la Enfermería, 2007)
The initial evaluation of the child, when admitted on the Paediatric Intensive Unit, is a essential tool and key piece as a starting point on the development of a specific Care Plan for each child. Therefore, it is necessary the existence of a protocol, according to a rigorous methodology, so that cares will have quality and thus, it will be avoided that each nursing professional will act in a different way, according to his intuition, beliefs or improvisation capacity.The initial evaluation of the child will allow us not only to coordinate the interventions, but also to give continuity to the cares.The initial evaluation of the child document is a nursing register that is part of the clinical register of the paediatric patient. Nursing registers turn to be the best approximation of what nowadays is our job's practice, and they are, therefore, necessary for us to be judged by a professional perspective and to make it possible to classify the services we carry out to the society.